Urban sports fields support higher levels of soil butyrate and butyrate‐producing bacteria than urban nature parks - Joel E. Brame; Craig Liddicoat; Catherine A. Abbott; Christian Cando‐Dumancela; Nicole W. Fickling; Jake M. Robinson; Martin F. Breed (Ecology and Evolution)
Abstract Butyrate‐producing bacteria colonise the gut of humans and non‐human animals, where they produce butyrate, a short‐chain fatty acid with known health benefits. Butyrate‐producing bacteria also reside in soils and soil bacteria can drive the assembly of airborne bacterial communities (the aerobiome). Aerobiomes in urban greenspaces are important reservoirs of butyrate‐producing bacteria as they supplement the human microbiome, but soil butyrate producer communities have rarely been examined in detail. Here, we studied soil metagenome taxonomic and functional profiles and soil physicochemical data from two urban greenspace types: sports fields (n = 11) and nature parks (n = 22). We also developed a novel method to quantify soil butyrate and characterised the in situ activity of butyrate‐producing bacteria. We show that soil butyrate was higher in sports fields than nature parks and that sports fields also had significantly higher relative abundances of the terminal butyrate production genes buk and butCoAT than nature parks. Soil butyrate positively correlated with buk gene abundance (but not butCoAT). Soil moisture (r = .50), calcium (r = −.62), iron (ρ = .54), ammonium nitrogen (ρ = .58) and organic carbon (r = .45) had the strongest soil abiotic effects on soil butyrate concentrations and iron (ρ = .56) and calcium (ρ = −.57) had the strongest soil abiotic effects on buk read abundances. Overall, our findings contribute important new insights into the role of sports fields as key exposure reservoirs of butyrate producing bacteria, with important implications for the provision of microbiome‐mediated human health benefits via butyrate.